Mobile Responsive App—A Useful Additional Tool for Data Collection in the German Pregnancy Register Rhekiss? - Richter, Jutta G.; Weiß, Anja; Bungartz, Christina; Fischer-Betz, Rebecca; Zink, Angela; Schneider, Matthias; Strangfeld, Anja (Frontiers in Medicine, 2021)
Background: The German pregnancy register Rhekiss is designed as a nationwide, web-based longitudinal observational cohort established in 2015. The register follows women with inflammatory rheumatic disease prospectively from child wish or early pregnancy until two years postpartum. Information on clinical and laboratory parameters, drug treatment, and (adverse) pregnancy outcomes are documented in pre-specified intervals. Physicians and patients report data for the same time periods via separated accounts and forms into a web-based application. As data entry on mobile devices might improve patients’ response rates, a responsive app as a further convenient documentation option was developed. Methods: The Rhekiss-app is available for self-reported data retrieval since 08/2017 from the App stores. For the current analysis, Rhekiss register data were used from the start of the register until September 30th 2020. Analyses were performed for forms containing information on devices. Outcome parameters were compared for mobile and desktop user for quantity and quality of filled forms. Results: 5,048 forms were received submitted by 966 patients. 57% were sent from mobile devices with highest numbers in patients with child wish (63%). Users of mobile devices were slightly younger and had less often a high educational level (62% vs 79%) compared to desktop users. The proportion of forms submitted via mobile devices increased steadily from 48% in the 4th quarter 2018 to 64% in the 3rd quarter 2020. The proportion of forms received before and after the Rhekiss-app implementation increased with the highest increase of 12% for forms filled at time point 12 months postpartum. Mobile users submitted significantly more forms than desktop users (2.9 vs 2.1), data send via desktops were more often complete (88% vs 86%). Conclusion: The responsive app is a valuable additional tool for data collection and well accepted by patients as indicated by its increasing use in Rhekiss. Apart from desktop/browser developments, technological adoptions within observational cohorts and registries should take smartphone requirements and developments into account, especially when patient-reported data in young, mobile patients are collected, bearing in mind that data quality could be compromised and concepts for improving data quality should be implemented.